KONSEKUENSI INOVASI DARI KARYA INOVASI BERBASIS PENYUSUNAN PERANGKAT BAHAN AJAR MATEMATIKA BALOK 3D PADA MAHASISWA PGMI - Muthia Salsabila; Nur Elisa Addina; Aniqah Alda Fuadiah; Asep Ediana Latip (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze various forms of innovation consequences experienced by PGMI students after compiling a set of 3D block-based mathematics teaching materials using the Rogers innovation consequence theory framework. The consequences studied include anticipated and unanticipated consequences, desirable and undesirable consequences, direct and indirect consequences, increase and decrease equality consequences, as well as stable equilibrium, dynamic equilibrium, and disequilibrium Consequences. This study uses a quantitative approach with a survey method. The research instrument in the form of a questionnaire contains 28 statements developed based on eleven categories of innovation consequences and filled in by 33 students in the third semester of the PGMI Study Program who have participated in the preparation of 3D block teaching materials. The results of the study show that the majority of students experience positive innovation consequences, especially in the aspects of anticipated, desirable, direct, indirect, and stable and dynamic equilibrium consequences. The innovation of 3D blocks contributes to increasing the understanding of geometry concepts, active engagement, high-level thinking skills, and students' adaptive and reflective attitudes in learning. However, this study also found unanticipated and undesirable consequences in the form of technical constraints and time constraints. Overall, the findings of the study show that students experience a diverse process of innovation adaptation, which not only strengthens pedagogical and professional competence as prospective Madrasah Ibtidaiyah teachers but also trains problem-solving skills in facing the challenges of implementing innovative learning.